PERSPECTIVES REGARDING THE USAGE OF TECHNOLOGY IN THE HOTEL INDUSTRY - ALEXANDRU CRISTIAN DOBRE (Annals of the University of Petrosani: Economics)
The pervasive integration of technology into the daily lives of individuals and organizations has been a longstanding phenomenon, marked by continual evolution. This progression inherently contributes to novel responses and solutions addressing societal challenges. However, it concurrently poses challenges in maintaining currency within the technological landscape and discerning the most recent and suitable solutions available. The imperative has shifted beyond a mere comprehension of the necessity and advantages associated with technological tools, extending to a nuanced understanding of the specific tools and their optimal utilization for maximum efficacy. Within the realm of hospitality, the trajectory of technological evolution has been notably conspicuous, spanning from the introduction of initial equipment in the nineteenth century to the contemporary application of Artificial Intelligence. Within this dynamic milieu, the concept of Digital Transformation emerges, denoting the systematic leveraging of technology to enhance organizational efficiency and competitiveness across various domains, including management processes, operationalization, and customer relationships. In the hospitality sector, and more broadly within the tourism industry, customer interaction assumes paramount significance. This is particularly salient given the nature of the industry, wherein human contact and interpersonal relationships play a pivotal role in shaping the tourist experience and influencing levels of consumer satisfaction.